Salivary cortisol concentrations in institutionalized and noninstitutionalized elderly people - Saliba, Tânia Adas [UNESP]; Machado, Ana Carolina Bernardes [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2018)
Introduction: due to the limitations inherent to the process of aging, institutionalization is a reality which may have an impact on the physical and psychological health status of elderly people. Objectives: determine salivary cortisol concentrations in institutionalized and noninstitutionalized elderly people, and verify variables such as oral health and physical dependence. Methods: a descriptive analytical cross-sectional study was conducted of a sample of 80 individuals, of whom 45 were institutionalized and 35 non-institutionalized. Oral clinical examination was performed to evaluate the use of and need for dental prostheses in the upper and lower arches. Saliva was collected to determine the concentration of cortisol, a biological marker of stress levels. Results: most of the sample were totally edentulous elderly people: 84.44% in the institutionalized group and 71.43% in the non-institutionalized group. A lower rate of prosthesis use was found in the institutionalized sample than in the noninstitutionalized sample (p= 0.0013). Analysis of salivary cortisol concentrations revealed significant differences between the groups, with higher values in the institutionalized group (p= 0.0397). Higher salivary cortisol concentrations were found among individuals with prosthetic needs, the difference being statistically significant (p= 0.0454). Conclusions: institutionalized elderly people had higher salivary cortisol concentrations, greater prosthetic needs, and were more care dependent than the non-institutionalized group.
Concentraciones de cortisol salival de ancianos institucionalizados y no institucionalizados
Concentrações de cortisol salivar de idosos institucionalizados e não institucionalizados
Keywords: Aging; Elderly people; Hydrocortisone; Nursing home; Oral health